ความสัมพันธ์ระหว่างปัจจัยการบริหารกับประสิทธิผลการบริหารงานวิชาการ ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษานครพนม เขต 1 - Bouchum, Peerapong; Hanrin, Chanwit; Puangyod, Paitoon (Journal of Graduate School Sakon Nakhon Rajabhat University, 2021)
The objectives of this research were: 1) to examine the level of school administrative factors, 2) to investigate the level of effectiveness of school academic affairs administration, 3) to identify the relationship between the administrative factors and the effectiveness of academic affairs administration in schools under the Nakhon Phanom Primary Educational Service Area Office 1, as perceived by school administrators, heads of academic affairs administration and teachers, and 4) to determine the predictive power of administrative factors affecting the effectiveness of academic affairs administration in schools under the Nakhon Phanom Primary Educational Service Area Office 1. The sample group consisted of school administrators, heads of academic administration and teachers, yielding a total of 338 participants. The tools for data collection were two sets of questionnaires. The statistics for data analysis were percentage, mean, standard deviation, Cronbach's alpha coefficient, Pearson's correlation coefficient, and stepwise multiple regression analysis. The research results revealed that: 1. the level of school administrative factors was overall at the highest level. 2. the level of the effectiveness of school academic affairs administration was overall at a high level. 3. The school administrative factors and effectiveness of school academic affairs administration had a positive correlation at a high level. 4. the school administrative factors were able to predict the effectiveness level of school academic affairs administration under the Nakhon Phanom Primary Educational Service Area Office 1 with the predictive power of 80 percent and a forecasting error of 0.15. The equations were written as follows: the equation in raw scores = 0.23 + 0.32X4 + 0.31X5 + 0.25X3 + 0.10X2 + 0.06 X7 the equation in standard form y = 0.36 ZX4 + 0.35 ZX5 + 0.27 ZX3 + 0.10 ZX2 + 0.06 ZX7